Two new species and two new records of Onychiurinae (Collembola, Onychiuridae) from the Nilgiris, India - Thunnisa, Abu Muhsina; Arbea, Javier Ignacio; Sumithra, Nallathambi; Mandal, Guru Pada; Sanil, Raveendranathanpillai (Zootaxa, 2022)
Four species of Onychiurinae are reported from the Nilgiris, Western Ghats, southern India, including two new species, Thalassaphorura udagaiensis sp. nov. and Protaphorura sholai sp. nov., and two new records for India: Protaphorura fimata (Gisin, 1952) and Orthonychiurus folsomi (Schäffer, 1900). Thalassaphorura udagaiensis sp. nov. can be separated easily from the similar species T. encarpata by the presence of 10/011/221110 dorsal S-chaetae and shorter anal spines. Protaphorura sholai sp. nov. is the most similar to the species P. microtica, P. subarctica and P. levantina as having the same number of ventral pseudocelli and parapseudocelli on abdomen; it can be easily distinguished by the position of head chaeta p2 in relation to p1 and p3, shorter M and Sp chaetae on Abd V and longer anal spines. We also sequenced the mitochondrial barcode region of cytochrome oxidase I (658 base pairs) to confirm the species status.